2007
DOI: 10.2519/jospt.2007.2292
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Anticipation on Movement Patterns in Subjects With ACL Deficiency Classified as Noncopers

Abstract: t MetHoDS anD MeaSuReS: The study included 16 subjects who are ACL deficient, classified as noncopers, and 20 healthy controls. Data were collected using an Optotrak Motion Analysis System and force plate integrated with Motion Monitor Software to generate knee joint angles, moments, and power. Each testing session included anticipated tasks, straight walking task (ST), and 45° side-step cutting tasks (SSC), followed by a set of unexpected straight walking (STU) and unexpected sidestep cutting (SSCU) tasks in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
13
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 45 publications
1
13
0
Order By: Relevance
“…Noncopers seem to utilize a common abnormal movement pattern of lower knee extensor loading even during unanticipated tasks. 33 Functional outcomes further suggest that a subgroup of noncopers require additional supervised rehabilitation to pass stringent criteria to return to sports. 28 Studies have revealed significant differences in angle-specific knee torque values between potential copers and noncopers (P<.05).…”
Section: Differences Between Copers and Noncopersmentioning
confidence: 99%
See 1 more Smart Citation
“…Noncopers seem to utilize a common abnormal movement pattern of lower knee extensor loading even during unanticipated tasks. 33 Functional outcomes further suggest that a subgroup of noncopers require additional supervised rehabilitation to pass stringent criteria to return to sports. 28 Studies have revealed significant differences in angle-specific knee torque values between potential copers and noncopers (P<.05).…”
Section: Differences Between Copers and Noncopersmentioning
confidence: 99%
“…Individuals in the coper group preferentially used a particular vastus lateralis and medial hamstrings activation pattern at a frequency more than twice that observed in the control group. 33,34 The noncoper group, compared to the control group, also preferentially used a medial hamstrings activation pattern more than twice as often and utilized a distinct medial hamstrings and lateral hamstrings activation pattern.…”
Section: Differences Between Copers and Noncopersmentioning
confidence: 99%
“…With regard to the knee, injury can result in destruction of mechanoreceptors (Bali, et al, 2012). Loss of mechanoreceptors after knee injury is associated with impaired joint-muscle reflexes and abnormal movement patterns (Beard, Kyberd, O'Connor, Fergusson, & Dodd, 1994;Houck, De Haven, & Maloney, 2007;Wojtys & Huston, 1994). Consequently, authors have described how impaired proprioception is a potential contributing factor to first-time joint injury, repetitive joint injury, and the onset and progression of osteoarthrosis (OA) (Borsa, Sauers, & Lephart, 1999;Felson, et al, 2009;MV Hurley, 1997;Roos, Herzog, Block, & Bennell, 2011;Segal, et al, 2010).…”
mentioning
confidence: 95%
“…The purpose of this study was to identify differences in the relationship of individual muscle activations and internal joint moments between ACLi participants and uninjured CON using a reliable isometric weight‐bearing force matching protocol . Consider that (1) greater knee abduction angles and internal moments; (2) greater knee rotation angles and internal moments; and (3) reduced knee flexion angles and greater knee extension internal moments are defining factors in the non‐contact ACL injury mechanism, and are associated with reports of ACLi knee instability . Therefore, compared to CON, ACLi muscle activations that have a greater relationship with internal knee abduction, rotation, and extension moments can be considered strategies that reduce knee joint stability, while muscle activations that have a greater relationship with internal knee adduction and flexion moments are considered strategies that increase knee joint stability.…”
mentioning
confidence: 99%